ANALYSIS THE IMPACT OF ENCLOSING VARIOUS MATERIALS ON THE STRENGTH OF WIFI SIGNAL RECEPTION - Rizki Akbar Rabbani, Adil Nurhaqqi; Yacoub, Redi Ratiandi; Marpaung, Jannus (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2023)
Installation Wi-Fi is sometimes hindered by obstacles such as wood, concrete, and glass. The presence of these materials may affect the signal strength received by the user. Therefore, research was carried out by enclosing router using PVC, acrylic and glass materials with a thickness of 2mm, 3mm and 5mm and a distance of 2m, 4m, 6m, 8m, 10m, 12m, 10.2m and 11.4m for RSSI measurements and Quality of Service at a distance of 12m and 11.4m in the morning, afternoon and evening. The measurement results show a decrease in RSSI depending on the obstacle and distance. This is because the signal experiences diffraction and reflection which causes the signal strength to weaken and the farther the distance the weaker the signal. Measurements at the moment non-line of sight has quite poor results, especially when the glass barrier with a thickness of 5mm is at a distance of 11.4 with an average RSSI value of 74.6 dBm. QoS parameter results show Throughput When video streaming all have a bad category due to low number of packets. Parameter Packet Loss all of them are in a very good category, showing the least missing packets. Parameter Latency all of them have a very good category though Throughput low, influenced by the number of incoming packets. Parameter Jitter good with 2mm and 3mm barriers, while 5mm in the afternoon is moderate, influenced by Latency.